Functional Human CD141+ Dendritic Cells in Human Immune System Mice. (25th October 2019) - Coelho-Dos-Reis, Jordana G A; Funakoshi, Ryota; Huang, Jing; Pereira, Felipe Valença; Iketani, Sho; Tsuji, Moriya
Abstract: Background: For the purpose of studying functional human dendritic cells (DCs) in a humanized mouse model that mimics the human immune system (HIS), a model referred to as HIS mice was established. Methods: Human immune system mice were made by engrafting NOD/SCID/IL2Rgamma null (NSG) mice with human hematopoietic stem cells (HSCs) following the transduction of genes encoding human cytokines and human leukocyte antigen (HLA)-A2.1 by adeno-associated virus serotype 9 (AAV9) vectors. Results: Our results indicate that human DC subsets, such as CD141 + CD11c + and CD1c + CD11c + myeloid DCs, distribute throughout several organs in HIS mice including blood, bone marrow, spleen, and draining lymph nodes. The CD141 + CD11c + and CD1c + CD11c + human DCs isolated from HIS mice immunized with adenoviruses expressing malaria/human immunodeficiency virus (HIV) epitopes were able to induce the proliferation of malaria/HIV epitopes-specific human CD8 + T cells in vitro. Upregulation of CD1c was also observed in human CD141 + DCs 1 day after immunization with the adenovirus-based vaccines. Conclusions: Establishment of such a humanized mouse model that mounts functional human DCs enables preclinical assessment of the immunogenicity of human vaccines in vivo. Abstract : Our current study has demonstrated the phenotype and function of human DCs, in particular, human CD141 + CD11c + and CD1c + CD11c + DCs, in a humanized mouse model, which may facilitate the future preclinical assessment of the immunogenicity of human vaccines in vivo.